Tinjauan Hukum Putusan Sela dalam Bentuk Schorsing pada Pengadilan Tata Usaha Negara - Dezonda R Pattipawae; Heillen M. Y. Tita (Perspektif Hukum, 2017)
The postponement of a State Administrative Decision which becomes the object of the dispute may be granted, since there is still a continuous factual action to be taken, namely the appointment of a definitive Regional Secretary, the inauguration or handover of the position of the dismissed Regional Secretary to the appointed Secretary of the Region whose contents as statements (declarations) of submission of all duties, powers and duties. Decree of the Governor of Maluku Number: 125.a Year 2014 dated May 20, 2014 concerning the Transfer of Civil Servants, on behalf of Kapressy Charles, SH. MSi, NIP: 19560911 198603 1 009 from Southwest Maluku District in Tiakur to the Government of Povinsi Maluku in Ambon, so Kapressy Charles, SH. Msi, felt his interest was damaged by the decision issued by the Governor of Maluku as the State Administration Officer. Therefore the concerned filed a lawsuit to the State Administrative Court of Ambon with Case No. 23/G/2014/PTUN.ABN, concerned requested to carry out the postponement of the transfer from the Government of the Southwest Maluku District to the Government of Maluku Province in due to the contradiction of the principles general good governance or prevailing laws and regulations.